The Development of an Effective Model for Implementing Information Management Strategies in Higher Education Institutions - Nimnual, Nattachai; Rugchatjaroen, Krish (Asian Crime and Society Review, 2020)
This research aimed to: 1) study the components of the information technology management strategies’ implementation in higher education institutions; 2) develop an effective model for information management strategies’ implementing in higher education institutions. This research used quantitative research methodology. The study indicated that there were 8 components of the information technology management strategies’ implementation in higher education institutions which was, database development and information system security, budget allocation, information systems strategic assignment and review before implementation, leadership, organizational culture, organizational capabilities, internal communication and rewards an incentives. The result of Bartlett’s Test of Sphericity includes all components in accordance of Chi-Square statistically significant at the 0.05 level and the Kaiser-Meyer-Olkin Measure of Sampling Adequacy was 0.850. The result of the development an effective model for information management strategies’ implementing showed that causal relationship was consistent with the empirical data. The first three of causal factors which had directly influence on organizational capabilities was internal communication, information systems strategic assignment and review before implementation and leadership. And the causal factors which had influence on organizational capabilities was information systems strategic assignment and review before implementation, leadership and organizational culture.